The significance of user-defined identifiers in Java source code authorship identification - Frantzeskou, G; MacDonell, SG; Stamatatos, E; Georgiou, S; Gritzalis, S (CRL Publishing Ltd, 2011)
When writing source code, programmers have varying levels of freedom when it comes to the creation and use of identifiers. Do they habitually use the same identifiers, names that are different to those used by others? Is it then possible to tell who the author of a piece of code is by examining these identifiers?
Keywords: Program Identifiers; Java; Source code; N-gram; Authorship Identification